2013
DOI: 10.5902/2179460x11350
|View full text |Cite
|
Sign up to set email alerts
|

Efeito Do Acoplamento Dos Modelos Numéricos Roms-WRF Na Camada Limite Planetária – Um Estudo De Caso Sobre a Confluência Brasil-Malvias

Abstract: 1 LMQA/CEPSRM/UFRGS -Porto Alegre -Rio Grande do Sul -2 GMO/CPTEC/INPE -São José dos Campos -São Paulo 3 gabriel.munchow@ufrgs.br RESUMO A camada limite planetária (CLP), região da atmosfera na qual habitamos, é fortemente regida pela interação com a superfície terrestre. Neste trabalho foi estudado o efeito na CLP da confluência Brasil-Malvinas utilizando o COAWST, um modelo numérico acoplado oceano-atmosfera-ondas-transporte de sedimentos. Para isso foi realizado dois experimentos, um somente com o modelo CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Together with in‐situ data, satellite observations, and atmospheric general circulation models, regional models have been widely used in studies of ocean–atmosphere interactions (e.g., Spall, 2007; O'Neill et al, 2010; Camargo et al, 2013; Kilpatrick et al, 2014; Pezzi et al, 2022; Pezzi et al, 2023). In the BMC region, by comparing two numerical experiments, the first with a coupled ocean–atmosphere model and the second with only the atmosphere model, Münchow et al (2013) showed an intensification in the horizontal gradients of wind, the equivalent potential temperature, and the vertical wind shear when using the coupled ocean–atmosphere model. The cyclone Catarina that occurred in the SWA in 2004 was used as a case study by Pullen et al (2017); they also compared atmospheric model and coupled ocean–atmosphere model simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Together with in‐situ data, satellite observations, and atmospheric general circulation models, regional models have been widely used in studies of ocean–atmosphere interactions (e.g., Spall, 2007; O'Neill et al, 2010; Camargo et al, 2013; Kilpatrick et al, 2014; Pezzi et al, 2022; Pezzi et al, 2023). In the BMC region, by comparing two numerical experiments, the first with a coupled ocean–atmosphere model and the second with only the atmosphere model, Münchow et al (2013) showed an intensification in the horizontal gradients of wind, the equivalent potential temperature, and the vertical wind shear when using the coupled ocean–atmosphere model. The cyclone Catarina that occurred in the SWA in 2004 was used as a case study by Pullen et al (2017); they also compared atmospheric model and coupled ocean–atmosphere model simulations.…”
Section: Introductionmentioning
confidence: 99%